2015
DOI: 10.1002/star.201400200
|View full text |Cite
|
Sign up to set email alerts
|

The physical and adsorption properties of different modified corn starches

Abstract: In order to improve the physical and adsorption properties of native corn starch, porous starch was prepared. Furthermore, dual‐modification of starches – enzyme hydrolyzed starch followed by cross‐linking as well as enzyme hydrolysis upon cross‐linking was explored. The results suggested that enzyme hydrolyzed starch followed by cross‐linking was significantly different from enzyme hydrolysis upon cross‐linking. The granular specific surface area of the dual‐modified starches was more than thousand orders of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…According to earlier studies, the nitrogen porosimetry analysis confirmed that all enzymatic conditions investigated have an increasing effect on the specific surface area, total pore volume, as well as pore size (Table ). In disregarding the three enzymatic conditions applied with a reaction time of 12 h, the porous starches presented a specific surface area of 2.3–4.0 times and total pore volume of 8.8–21.0 times higher when compared to the native sample, being most expressive in the AM + AMG6 sample.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…According to earlier studies, the nitrogen porosimetry analysis confirmed that all enzymatic conditions investigated have an increasing effect on the specific surface area, total pore volume, as well as pore size (Table ). In disregarding the three enzymatic conditions applied with a reaction time of 12 h, the porous starches presented a specific surface area of 2.3–4.0 times and total pore volume of 8.8–21.0 times higher when compared to the native sample, being most expressive in the AM + AMG6 sample.…”
Section: Resultssupporting
confidence: 68%
“…This behavior occurs because the amorphous region is relatively exposed and accessible at the surface of the granules . As reported in previous studies, α‐amylases (AM) are endo‐amylases that randomly cleave internal α(1,4) glucosidic bonds of the polysaccharide chains and β‐amylases are exo‐amylases, which cleave α(1,4) glucosidic bonds from the non‐reducing ends of the starch chain. Glucoamylases (amyloglucosidases, AMG) are exo‐amylases that can act on both α(1,4) and α(1,6) glucosidic bonds from the non‐reducing ends of the starch chain and isoamylases are debranching enzymes that hydrolyze exclusively α(1,6) glucosidic bonds, leaving long linear polysaccharides.…”
Section: Introductionmentioning
confidence: 75%
“…The obtained results indicate that starches 12650 and 12616 were characterised by less porous surfaces of molecules, and capillaries prevailing on their surfaces were characterised by lower sizes as compared to 06748. The obtained values were within the ranges of 0.42±0.01 for native maize starch and 684.5±0.12 for enzyme hydrolysed starch followed by cross-linking, specified by Guo et al (2015) for different types of maize starch.…”
Section: Resultssupporting
confidence: 60%
“…The thermal analysis was performed according to previous methods (Liu et al, 2006(Liu et al, , 2009Guo & Du, 2014;Guo, Liu, Li, Sun, & Du, 2015) with proper modifications. The gelatinisation temperatures including onset temperature (T o ), peak temperature (T p ), conclusion temperature (T c ) and gelatinisation enthalpy (DH) were measured using a PerkinElmer DSC8000 Thermal Lab System.…”
Section: Thermal Analysismentioning
confidence: 99%